GAMBARAN POLA PENCEMAR UDARA DI WILAYAH SEKITAR BUNDARAN HOTEL INDONESIA TAHUN 2017 - Suci Tresnasari; Budiyono Budiyono; Suhartono Suhartono (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Bundaran Hotel Indonesia was a Central Business District (CBD) with the poor air quality. It was as a resultof this condition. In 2017, the total of “unhealthy”days had increased from 2 to 28 days. This indicated that the air quality was getting worse. Meteorology factor influencedthe pattern of air pollutants. The purpose of this study was todescribethe pattern of air pollutants in Bundaran HI and the surrounding area in 2017.This research was a descriptive analytic with cross sectional approach. The data analysis from this research used Rank Spearman. The secondary data of pollutant were taken from Daily Mean Value (DMV)from Dinas Lingkungan Hidup DKI Jakarta Province. The results showed that the average concentration of air pollutants were 50,60 µg/m3for PM10, 25,36 µg/m3 forSO2,1,79 mg/m3 for CO, 48,81 µg/m3for O3, and 12,70 µg/m3 for NO2. There was a significant correlation between wind speed and the level of PM10 (p=<0,0001,r=-0,444), O3 (p=<0,0001,r=-0,499), NO2 (p=<0,0001,r=-0,644). There was significant correlation between humidity and level of SO2 (p=<0,0001,r=-0,379) and CO (p=<0,0001,r=0,468). Wind speed and humidity contributed to air pollutants (PM10, SO2, CO, O3, NO2).